Recent Evidence on Acute Kidney Injury in COVID-19 Patients: A Narrative Review - Herleni Kartika; Novadian Suhaimi; Zulkhair Ali; Suprapti; Ian Effendi; Harun Hudari; Mega Permata; Nelda Aprilia Salim; Eddy Yuristo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
The pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The clinical manifestation of COVID-19 is broad, ranging from an asymptomatic carrier state to severe disease leading to the death penalty. There is also emerging evidence that kidneys are affected early in COVID-19. Proteinuria and haematuria have been reported in 44% and 26.7% on admission, respectively. This literature review shows clinical manifestations of acute kidney injury (AKI) in a patient with COVID-19 infection. Literature reviews are carried out on various sources found on Google Scholar and Pubmed to search for articles, journal research, case reports, systematic reviews, meta-analyses, and textbooks. Various studies demonstrate the possibility of coronavirus infecting the kidney with several mechanisms such as cytokine storm syndrome (CSS), direct viral infection, and imbalance of renin-angiotensin-aldosterone (RAAS). Haematuria and proteinuria are associated with higher mortality and may signify aggressive disease early. Thus all patients should have a baseline urinalysis. There is a number of different causes of AKI in COVID-19, and some mechanisms by which COVID-19 affects kidneys remain unclear.